2020
DOI: 10.1126/sciimmunol.aba9953
|View full text |Cite
|
Sign up to set email alerts
|

A distinct GM-CSF + T helper cell subset requires T-bet to adopt a T H 1 phenotype and promote neuroinflammation

Abstract: Elevation of granulocyte-macrophage colony-stimulating factor (GM-CSF)–producing T helper (TH) cells has been associated with several autoimmune diseases, suggesting a potential role in the pathogenesis of autoimmunity. However, the identity of GM-CSF–producing TH cells has not been closely examined. Using single-cell RNA sequencing and high-dimensional single-cell mass cytometry, we identified eight populations of antigen-experienced CD45RA−CD4+ T cells in blood of healthy individuals including a population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
(79 reference statements)
2
32
0
Order By: Relevance
“…22 A frequent observation in human studies and murine inflammatory disease models, including GVHD, has been the identification of heterogeneous populations of CD4 + GM-CSF + T cells in tissue culture and in vivo within specific target tissues; specifically, those that make GM-CSF alone or cells that produce GM-CSF in conjunction with other T H -defining cytokines, most often IFN- or IL-17. 6,7,[23][24][25][26] This finding has raised the question as to whether these cells constitute a subset of T H 1 and/or T H 17 cells, or if there exists a distinct T H GM-CSF subset within this heterogenous population that differentiate these cells ontologically from more classically defined T H 1 and T H 17 cells. 27 To date, however, characterization of CD4 + GM-CSF + T cell heterogeneity within specific tissue sites in inflammatory diseases such as GVHD has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…22 A frequent observation in human studies and murine inflammatory disease models, including GVHD, has been the identification of heterogeneous populations of CD4 + GM-CSF + T cells in tissue culture and in vivo within specific target tissues; specifically, those that make GM-CSF alone or cells that produce GM-CSF in conjunction with other T H -defining cytokines, most often IFN- or IL-17. 6,7,[23][24][25][26] This finding has raised the question as to whether these cells constitute a subset of T H 1 and/or T H 17 cells, or if there exists a distinct T H GM-CSF subset within this heterogenous population that differentiate these cells ontologically from more classically defined T H 1 and T H 17 cells. 27 To date, however, characterization of CD4 + GM-CSF + T cell heterogeneity within specific tissue sites in inflammatory diseases such as GVHD has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirmed that IL-1b signaling is not necessary for Th17 development, but rather for GM-CSF expression by Th cells. Even though IL-1b has a strong GM-CSF-inducing effect, GM-CSF expression by Th cells was not abrogated without IL-1b signaling, indicating that other cytokines, such as IL-2, IL-7, and IL-23 (28), also induce GM-CSF expression. The relationship between IL-1b and GM-CSF is reciprocal, as GM-CSF induces IL-1b expression in myeloid cells and the lack of GM-CSF drastically reduces IL-1b expression by monocytes in the CNS of mice with EAE.…”
Section: Discussionmentioning
confidence: 98%
“…We show that in the CNS of mice with EAE, rIFN-b treatment induces similar monocyte subset with pDC-like phenotype, expressing IFN-b, type-I IFN-related genes, PDCA-1, and Siglec-H. pDCs are known as the major source of IFN-b, but monocytes/macrophages can also produce IFN-b during viral infections and in EAE (53)(54)(55)(56). Given that pDCs have an (45), was initially associated with the development of Th17 cells (61), but more recent studies emphasize its role in promoting GM-CSF expression by Th cells (26,28). Our results confirmed that IL-1b signaling is not necessary for Th17 development, but rather for GM-CSF expression by Th cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations